The avengers and the PLA wolf warrior: popular narratives and major power competition - Ho, Benjamin Tze Ern (2022)
In recent years, some scholars of international politics have argued for the need to integrate the use of visual media into our understanding of global politics. In this respect, film (or movies) represents an effective media of communicating powerful ideas and political worldviews through a smorgasbord of sound and sensory experiences. This essay seeks to draw on the theoretical insights of scholars of visual international politics to analyze the ongoing geopolitical conflict between the United States and China. It will do so by examining two box-office hits in the West and China, namely, the Avengers and Wolf Warrior. Through a study of some of the key storylines in these films, this essay seeks to flesh out the differences in Sino-Western conceptions of patriotism, good and evil, and salvation. It argues that these differences are not just a matter of aesthetic preferences, but reflect more fundamental ideas and political worldviews salient in the thinking of China and the West.